Autonomic dysfunction in chronic inflammatory demyelinating polyradiculoneuropathy - Figueroa, J.J. (Lippincott Williams & Wilkins, 2012)
OBJECTIVES: Autonomic deficits in chronic inflammatory demyelinating polyradiculoneuropathy (CIDP) have not been adequately quantitated. The Composite Autonomic Severity Score (CASS) is a validated instrument for laboratory quantitation of autonomic failure derived from standard autonomic reflex tests. We characterized dysautonomia in CIDP using CASS. METHODS: Autonomic function was retrospectively analyzed in 47 patients meeting CIDP criteria. CASS ranges from 0 (normal) to 10 (pandysautonomia), reflecting summation of sudomotor (0–3), cardiovagal (0–3), and adrenergic (0–4) subscores. Severity of neurologic deficits was measured with Neuropathy Impairment Score (NIS). Degree of small fiber involvement was assessed with quantitative sensation testing. Thermoregulatory sweat test (TST) was available in 8 patients. RESULTS: Patients (25 men) were middle-aged (45.0 ± 14.9 years) with longstanding CIDP (3.5 ± 4.3 years) of moderate severity (NIS, 46.5 ± 32.7). Autonomic symptoms were uncommon, mainly gastrointestinal (9/47; 19%) and genitourinary (8/47; 17%). Autonomic deficits (CASS ≥1) were frequent (22/47; 47%) but very mild (CASS, 0.8 ± 0.9; CASS ≤3, all cases). Deficits were predominantly sudomotor (16/47; 34%) and cardiovagal (10/47; 21%) with relative adrenergic sparing (4/47; 9%). TST was abnormal in 5 of 8 patients (anhidrosis range, 2%–59%). Sudomotor impairment was predominantly distal and postganglionic. Somatic deficits (disease duration, severity, small fiber deficits) did not predict presence of autonomic deficits. CONCLUSION: Our data characterize the autonomic involvement in classic CIDP as mild, cholinergic, and predominantly sudomotor mainly as a result of lesions at the distal postganglionic axon. Extensive or severe autonomic involvement (CASS ≥4) in suspected CIDP should raise concern for an alternative diagnosis.